Optimization and Analysis of Acid Treated Trimethylamine using Surface Response and Gas Chromatography Analytical Methods - Park, Seul-Ki; Khan, Fazlurrahman; Cho, Yeon-Jin; Hong, Dong-Lee; Jang, Yu-Mi; Kim, Young-Mog (Current Analytical Chemistry, 2020)
Background: Trimethylamine (TMA) is a nitrogenous base aliphatic organic compound accounting for the odor of rotten fish and it is used as an indicator for analyzing the quality of fish products. Introduction: Extraction procedures and analytical methods including colorimetric and Gas- Chromatography (GC) can quantify the TMA contents of fish products after pre-treatment with basic solutions. However, the extraction procedure and analytical methods for acid-treated samples are not known, despite the majority of fish products being preserved using acid preservatives. Methods: The methodologies used included solid-phase micro-extraction of TMA followed by its quantification by a GC-based analytical method. An analysis of response surface methodology was also conducted to verify the optimum conditions for TMA detection in acid-treated liquid samples affected by factors including trapping time, temperature, and stirring speed. Results: The results obtained from this study showed that the optimum conditions for the best yield of TMA extraction are 20 min of trapping, emission at 55°C, and stirring at 400 rpm. The validation of the developed method was carried out using rotten fish after acid treatment. Acid treatment decreased TMA by up to 73.01%, however, when adding NaOH solution of the same volume to the samples, TMA increased similar to the control group. Conclusion: Here, we report a simple, sensitive, and rapid extraction procedure. A GC-based analytical method was developed for the analysis of TMA from the acid-treated sample. The developed extraction procedure and analytical methods were optimized and validated, which could be helpful for the extraction of TMA without damaging the sample.
Keywords: gas chromatography